Rechargeable battery cell with improved high temperature performance - KOCH JOHN M; FIERRO CRISTIAN (2014)
An alkaline, rechargeable electrochemical cell includes a pasted electrode structure in which a composition comprising a paste matrix component includes cobalt in an amount greater than 6 weight percent ranging up to 14 weight percent. The matrix may also include a rare earth such as yttrium. The composition further includes particles of nickel hydroxide dispersed in the matrix, and these particles include cobalt levels ranging from greater than 8 atomic percent up to 15 atomic percent. Cells incorporating these materials have good charging efficiency at elevated temperatures.